The impact of branding on behavioural intention to study at a TVET college: a South African grade 12 leaner perspective - Dlamini, Siphiwe (My University, 2020)
Purpose – Building a brand with a strong consumer brand knowledge structure (BKS) (i.e. brand awareness and brand image) is what drives consumers’ positive response to the marketing of the brand, including behavioural intention. While the BKS of South African universities, such as the universities of Cape Town, Witwatersrand and Stellenbosch, is strong and yields benefits in terms of grade 12 students’ high preferences and intentions to study at these universities, little is known about the grade 12 learners’ BKS and its outcomes for Technical and Vocational Education and Training (TVET) colleges. The research study developed a conceptual model for the higher education sector to assess the explanatory power of BKS that TVET colleges have built. Particularly, the study examined the extent to which BKS impacted grade 12 learners’ intentions to study at a TVET college through brand reputation, brand heritage, brand symbolism and brand distinctiveness. It also assessed the mediating role of brand reputation, brand heritage, brand symbolism and brand distinctiveness in the relationship between BKS and intentions to study. Design/methodology/approach – The key literature on higher education branding was reviewed and relevant theories(self-congruity theory, theory of planned behaviour, self-identity theory and the customer-based brand equity theory) were evaluated to borrow ideas for the development of a conceptual model of this study. The proposed conceptual model was tested with data from a self-administered questionnaire, which was completed by 301 randomly selected grade 12 school learners from three secondary schools in Gauteng province. The data were analysed with Partial Least Squares (PLS) Structural Equation Modelling (SEM) using Smart PLS 3 software, as well as AMOS 25. Findings – With the exception of brand awareness, which is an element of BKS that did not significantly impact the intentions to study, brand image, the other element of BKS, significantly impacted intentions to study directly and indirectly through its significant impact on brand reputation, brand heritage, brand symbolism and brand distinctiveness. Brand reputation, brand heritage, brand symbolism and brand distinctiveness significantly mediated the relationships between brand awareness, brand image and intentions to study. This means that even though brand awareness cannot directly influence the intentions of grade 12 learners to choose to study at TVET colleges, if the awareness is translated into brand reputation, brand heritage, brand symbolism and brand distinctiveness, the intentions may develop. In terms of the explanatory power of BKS, the developed and tested conceptual model explained 58% of brand distinctiveness, 52% of brand heritage, 61.4% of brand reputation, 19.3% of brand symobolism and 31.1% of the behavioural intention to study at a TVET college. Implications – Theoritically, this study contributes to the field of brand management, service and institutional marketing by expanding and testing a customer-based brand equity (CBBE) conceptual model that can be suitable for measuring outcomes from BKS building efforts and investments. Practically, the study contributes by providing insights into the benefits TVET colleges could obtain if they continue to strengthen their investments in building brand awareness and image of what they can offer current and prospective students. Some of the benefits, as this study found, will be obtained from the building of brand heritage, brand reputation, brand symbolism and brand distinctiveness. While this study found that these brand constructs are important and significant drivers of the intentions to study at TVET colleges, they may lead to other benefits, such as students’ statisfaction, brand preferences and willingness to pay high fees, as some studies suggest. Originality/contribution – This study is one of the first investigations into the extent to which BKS developed by TVET colleges may influence intentions to study through a number of brand-related factors. On identifying the dimensions of CBBE that are important for higher education institutions, it was found that perceived quality, reputation, emotional/symbolic environment, brand loyalty and brand awareness were important in generating students’ positive responses. The current study adds value by examining the extent to which these factors can influence behavioural action, starting with intentions. The study enriches higher education literature by studying brand symbolism, brand reputation, brand heritage and brand distinctiveness in terms of their drivers (brand awareness and brand image) and outcome (intentions to study)
A thesis submitted in complete fulfilment of the requirements for the degree of the Doctor of Philosophy in Marketing in The School of Economic and Business Sciences, The University of the Witwatersrand, 2020